2008
DOI: 10.1590/s0100-29452008000200005
|View full text |Cite
|
Sign up to set email alerts
|

Estudo anatômico do crescimento do fruto em Acca sellowiana Berg.

Abstract: RESUMO -A Acca sellowiana Berg. (Myrtaceae) é uma frutífera nativa dos planaltos meridionais do Sul do Brasil e que se encontra em processo de domesticação. Seus frutos são doce-acidulados e podem ser consumidos in natura ou empregados para a produção de sucos e doces. Assim, informações sobre o desenvolvimento, morfologia e anatomia de seus frutos são de grande interesse e foram objetos do presente trabalho. O fruto (ovário mais hipanto), no tempo zero (plena floração), tem, em média, 0,6 cm de altura e 0,4 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 12 publications
2
7
0
1
Order By: Relevance
“…The fruit growth curve had three post-anthesis stages: the first stage of slow growth lasted approximately 80 days after anthesis in both of the sites; stage two included faster growth from day 80 until day 127 (2209 GDD) for San Francisco de Sales, and from day 80 until day 145 (1587 GDD) for Tenjo; stage three, in which the fruit weight increased significantly in both of the sites, lasted from day 127 until harvest and from day 145 until harvest for San Francisco de Sales and Tenjo, respectively. These results coincide with those found by Rodríguez et al (2006) for 'Quimba' pineapple guava and by Esemann-Quadros et al (2008), who conducted feijoa fruit studies in anatomy and morphology. Fischer (2003) showed that pineapple guava normally has a simple sigmoid growth curve (in size or weight) but can also express a double sigmoid depending on the cultivar and the agroecological conditions.…”
Section: Mathematical Models Of Thermal Time For Fruit Weightsupporting
confidence: 92%
See 1 more Smart Citation
“…The fruit growth curve had three post-anthesis stages: the first stage of slow growth lasted approximately 80 days after anthesis in both of the sites; stage two included faster growth from day 80 until day 127 (2209 GDD) for San Francisco de Sales, and from day 80 until day 145 (1587 GDD) for Tenjo; stage three, in which the fruit weight increased significantly in both of the sites, lasted from day 127 until harvest and from day 145 until harvest for San Francisco de Sales and Tenjo, respectively. These results coincide with those found by Rodríguez et al (2006) for 'Quimba' pineapple guava and by Esemann-Quadros et al (2008), who conducted feijoa fruit studies in anatomy and morphology. Fischer (2003) showed that pineapple guava normally has a simple sigmoid growth curve (in size or weight) but can also express a double sigmoid depending on the cultivar and the agroecological conditions.…”
Section: Mathematical Models Of Thermal Time For Fruit Weightsupporting
confidence: 92%
“…These authors observed that the growth curve of the fruit showed three stages after anthesis: the first stage from 70 days post-anthesis was the slow-growing phase; the second stage lasted from day 70 until day 126, and the third stage lasted from day 126 until day 154. The authors also demonstrated that during the third development stage, the fruit volume increased significantly in both of the clones, which corroborated findings from Esemann-Quadros et al (2008). Table 2.…”
Section: Individual Pineapple Guava Fruit-weight Equation As a Functisupporting
confidence: 81%
“…Aspectos anatômicos dessas etapas foram observados em células de frutos de goiabeira serrana (Acca selowiana, Myrtaceae), por Esemann-Quadros et al (2008). Giovannoni (2004) relata que, em tomate, considerado fruto climatérico, ocorreu a síntese e o acúmulo de pigmentos carotenoides, durante a maturação.…”
unclassified
“…The presence of sclereids in the mesocarp, as in C. adamantium has also been described in C. pubescens, Psidium australe var. argenteum, P. guianensis (Moreira‐Coneglian , ), and Acca selloviana (Esemann‐Quadros et al ). Despite the fact that this characteristic is referred to in the literature as of general occurrence for species of the ‘Pimenta’ group, which include the afore‐mentioned species, the presence of sclereids was not mentioned by Landrum ().…”
Section: Discussionmentioning
confidence: 99%